Helicobacter pylori and peptic ulcer disease--a causal link - Goh, Khean Lee (Malaysian Medical Association, 1997)
The link between Helicobacter. pylori and peptic ulcer disease in 1997 is an irrefutable one. The association between infection and ulcerogenesis has been shown to be biologically plausible with induction of epithelial inflammation and cell damage and its effect on gastrin/acid homeostasis. The association of H. pylori infection and peptic ulcer disease is a close and consistent one. There is ample evidence indicating that H. pylori eradication results in virtual abolition of ulcer relapse. Several studies have demonstrated that eradication of H. pylori results in ulcer healing and there is evidence showing a temporal relationship between infection and development of peptic ulcer disease.